Neutrophil-to-lymphocyte and Platelet-to-lymphocyte Ratio as Predictors of CD4 Count among People Living with HIV - Hasna, Zahra Roidah Amalia; Sunggoro, Agus Jati; Sri Marwanta; Harioputro, Dhani Redhono; Yimam Getaneh Misganie; Siti Qamariyah Khairunisa (Indonesian Journal of Tropical and Infectious Disease, 2024)
Human Immunodeficiency Virus (HIV) infection remains a global health concern characterized by the reduction of CD4 lymphocyte cells and weakened immune systems. Knowing the CD4 count and the factors affecting it is crucial for assessing the immune status of HIV patients. Hematological markers, including neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR), have been recognized as prognostic tools that were associated with CD4 Count. The goal of this study was to determine the impact of NLR and PLR on CD4 count among people living with HIV (PLHIV). This study used analytic observational method with a cross-sectional on HIV-positive individuals who were treated at Moewardi Hospital, Surakarta, Indonesia. The Chi-Square and Pearson correlation tests were performed to identify the correlation between variables and the linear regression test was done to investigate the association between NLR and PLR with CD4 count. A total of 80 PLHIV were identified for this study, with the median CD4 count of 103 cells/mm3. NLR and PLR were found to be 3.06 and 181.03, respectively. This study found that opportunistic infection, duration on ARV treatment, body mass index, total lymphocyte count, and hemoglobin were significantly associated with CD4 count. The Pearson correlation test revealed a strong correlation between NLR and PLR to CD4 count. Linear regression analyses showed that NLR and PLR could predict the CD4 count. These findings indicate that NLR and PLR could serve as alternative prognostic parameters for monitoring treatment outcomes in PLHIV, particularly in health facilities where access to CD4 count testing is limited.